Problems of legal uncertainty of the criminal law prohibition of unauthorized distribution of militarily significant information - Starko, O. L. (Аналітично-порівняльне правознавство, 2025)
The article is devoted to the problem of legal uncertainty of the criminal law prohibition of unauthorized distribution of militarily significant information. Attention is focused on the issues of identifying defects inherent in the analyzed norm and ways to eliminate them, difficulties and problems related to the application of this criminal law prohibition. The article draws attention to the question of the vagueness of the legislative formulation of the features of the subject of the crime under Part 1 of Art. 114-2 of the Criminal Code (hereinafter – the Criminal Code) of Ukraine in terms of belonging or not belonging to «weapons, weapons and ammunition» (information about which is distributed) to foreign military aid. A conclusion was made about the impracticality of using an indication of the origin of weapons, weapons, and ammunition in the disposition of the article. The question of the limitation of the legislative wording of the subject of the crime under Part 1 of Art. 114- 2 of the Criminal Code of Ukraine, according to which unauthorized dissemination of information about the movement, movement, location of such military equipment as airplanes, helicopters, drones, tanks, technical means of equipment protection, etc. remains outside the scope of the crime. It was established that despite the fact that in Part 2 of Art. 114-2 of the Criminal Code of Ukraine does not have the subject of a crime at all, the courts qualify the dissemination of information about the movement, location of airplanes, helicopters under Part 2 of Art. 114-2 of the Criminal Code of Ukraine. The inappropriateness of the simultaneous use in the disposition of the norm formulated in Art. 114-2 of the Criminal Code of Ukraine of such synonyms as «mov» and «displacement». Attention is focused on the expediency of using as a mandatory feature of the objective side of the composition of the crime such a feature as «special period and period of armed conflict». Problematic aspects of the application of Part 3 of Art. 114-2 of the Criminal Code, namely, the issue of delimiting the composition of the crime provided for in Part 3 of Art. 114-2 of the Criminal Code of Ukraine and treason committed under martial law (Part 2 of Art. 111 of the Criminal Code of Ukraine). Using the example of criminal legal assessment by courts of identical acts, the problematic nature of distinguishing the composition of the analyzed crime and treason is shown. It is proposed to exclude criminal liability for the dissemination of militarily significant information in order to provide such information to the state carrying out armed aggression against Ukraine, or its representatives, or other illegal armed formations, since this act is covered by Part 2 of Art. 111 of the Criminal Code of Ukraine.